2012
DOI: 10.1007/s10856-012-4596-4
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of titanium by hydrothermal treatment in Mg-containing solution and early osteoblast responses

Abstract: Surface modification on titanium was carried out in order to improve its bioactivity. Pure titanium was hydrothermally treated in distilled water and 0.1 M MgCl(2) solutions at 200°C for 24 h. Surface morphology, roughness, wettability and chemical composition were characterized before and after treatment. Bovine serum albumin was used as model to study protein adsorption. MC3T3-E1 cells were cultured and initial cell attachment, morphology, proliferation were evaluated. After hydrothermal treatment, nano-size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 44 publications
(47 reference statements)
0
41
0
Order By: Relevance
“…48 However, unlike the case of a fibroblast, a superhydrophilic surface favors the attachment of osteoblasts. 49 So the prepared samples with better wettability favor the formation of the tissue fragments and are easier to incorporate with the surrounding biological environment. 50 3.2.…”
Section: Resultsmentioning
confidence: 99%
“…48 However, unlike the case of a fibroblast, a superhydrophilic surface favors the attachment of osteoblasts. 49 So the prepared samples with better wettability favor the formation of the tissue fragments and are easier to incorporate with the surrounding biological environment. 50 3.2.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of bioactive trace elements such as calcium, silicon, zinc, strontium, and magnesium is frequently used. [14][15][16][17][18] These trace elements are able to stimulate bone growth and bone healing by enhancing osteoblast activity. [19][20][21] As one of the most abundant elements in the human body, 22 magnesium is essential for bone metabolism and stimulates new bone formation, and may also interact with integrins of osteoblasts, which are responsible for cell adhesion and stability.…”
mentioning
confidence: 99%
“…Previous studies demonstrated similar results where cells on Mg containing surfaces showed higher proliferation and differentiation compared to Mg-free specimens. 30,38,39 Furthermore, Mg ions are considered to be beneficial for bone cell attachment. Zreiqat et al 23 reported that cells grown on Mg-modified alumina exhibited a significantly increased adhesion since binding of integrins to specific ligands depends on the presence of divalent cations.…”
Section: Discussionmentioning
confidence: 99%